Avaliação de material particulado na recirculação de grãos de soja em silos - Mello, Augusto César de (2009)
This work presents a case study involving the problem in emission of particulate matter in units handling grain in an Agricultural Cooperative. The scenario above is the exhaust duct for dust from the gap to lift the silo for feeding of plant oils belonging to the Cooperative. The problem in question is the generation of dust to the environment external to the company from the movement of soybeans in storage local. To assess this issue, quantitative methods were used to characterize the particle size, concentration of dust, the presence of biological and chemical contaminants. The site was chosen for sampling the output of the exhaust duct, dividing it into 17 points distributed radially. For comparison it is assumed parameters outlined in Resolution SEMA 054/2006 for potential emission of Particulate Total, artigo 44. The identification of the problem and its variables makes it possible to measure solutions for minimizing air pollution produced by movement of soybeans in silos.